Analysis on applicability evaluation of forensic science standards in China - Hejuan Jiao; Xiaoyu Zheng; Yanbiao Zhao; Feng Hua; Hui Zheng (Journal of Forensic Science and Medicine, 2017)
Standard applicability is the ability of a standard to be suitable for the prescriptive purpose under specified conditions. There is no mature applicability-evaluation index system of standards worldwide at present. We aim to construct the index system for evaluating the applicability of forensic science standard. The index system of applicability evaluation is proposed using a statistical analysis on the applicability of forensic science standards in China. We summarize the major problems and reasons in developing and revising the national and industry standards in China. Based on these, we put forward measures to improve standards' applicability, provide policy support for rectifying the standards, and lay the theoretical foundation for the construction, adjustment, and optimization of the forensic science standard system.